(3TQM GdbhGYO GdNeSs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg hMOg GdPj LYd GdMQha UhQkG cGdCTHGM s
(3BNQgG (B:s
(3jYfj GYJOGd cdkG efgeG hGddg JYGdi CYOd hCMce s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B35s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B(58 (3c(B) s
Keywords: (3GdMQha h GdChaGbs